Breeding Contempt : The History of Coerced Sterilization in the United States - Largent, Mark A. (Book collections on Project MUSE., 2008)
From the Publisher: Most closely associated today with the Nazis and World War II atrocities, eugenics is sometimes described as a government-orchestrated breeding program, other times as a pseudo-science, and often as the first step leading to genocide. Less frequently is it depicted as a movement having links to America-a nation that has historically prided itself for its scientific rationality. But eugenics does have a history in the United States-a history that is largely the story of biologist Charles Davenport. Davenport, who led the Eugenics Records Office in the late nineteenth century, provided physicians, social scientists, and lawmakers with the scientific data and authority that enabled them to coercively sterilize men and women who were thought to be socially deviant, unfit to pass on their genes, and unable to raise healthy children. Moreover, Mark A. Largent shows how even in modern times, remnants of eugenics philosophies persist in this country as certain public figures advocate a brand of birth control-such as progesterone shots for male criminals-that are only steps away from the castrations that were once performed.